The importance of accounting for matedness when predicting the peak shear strength of rock joints. Issue 1 (August 2021) - Ríos-Bayona, F; Andersson, E; Johansson, F; Mas Ivars, D
Abstract: The contribution from both surface roughness and matedness in the peak shear strength of rock joints is not yet well understood. To be able to account for the influence of matedness on the peak shear strength of rock joints, both surface roughness and aperture need to be considered. Technical developments over the past few decades have shown that both surface roughness and aperture can be accurately measured using optical scanning. This technique has been utilized to account for surface roughness parameters in various shear strength criteria that assume a perfect match between joint surfaces. This paper investigates and compares the capabilities of two shear strength criteria to predict the peak shear strength of rock joints with different matedness. The analysis performed shows that both approaches have their strengths and limitations. For instance, accounting for the matedness of unmated rock joints based on their surface aperture gives better predictions of the peak shear strength. On the other hand, accounting for shearing failure mode becomes relevant at high normal loads. A possible way forward to reduce the limitations of these criteria could be to combine their strengths.